Impact of the chronic disease self-management program (CDSMP) on self-perceived frailty condition: the EU-EFFICHRONIC project - Sabrina Zora (SAGE Publishing, 2021)
Introduction: The Chronic Disease Self-Management Program (CDSMP) improves self-efficacy and health outcomes in people with chronic diseases. In the context of the EFFICHRONIC project, we evaluated the efficacy of CDSMP in relieving frailty, as assessed by the self-administered version of Multidimensional Prognostic Index (SELFY-MPI), identifying also potential predictors of better response over 6-month follow-up. Methods: The SELFY-MPI explores mobility, basal and instrumental activities of daily living (Barthel mobility, ADL, IADL), cognition (Test Your Memory-TYM Test), nutrition (Mini Nutritional Assessment-Short Form-MNA-SF), comorbidities, medications, and socio-economic conditions (social-familiar evaluation scale-SFES). Participants were stratified in three groups according to the 6-month change of SELFY-MPI: those who improved after CDSMP (Δ SELFY-MPI < 0), those who remained unchanged (Δ SELFY-MPI = 0), and those who worsened (Δ SELFY-MPI > 0). Multivariable logistic regression was modeled to identify predictors of SELFY-MPI improvement. Results: Among 270 participants (mean age = 61.45 years, range = 26–93 years; females = 78.1%) a benefit from CDSMP intervention, in terms of decrease in the SELFY-MPI score, was observed in 32.6% of subjects. SELFY-MPI improvement was found in participants with higher number of comorbidities (1–2 chronic diseases: adjusted odd ratio (aOR)=2.38, 95% confidence interval (CI) =1.01, 5.58; ⩾ 3 chronic diseases: aOR = 3.34, 95% CI = 1.25, 8.90 vs no chronic disease), poorer cognitive performance (TYM ⩽ 42: aOR = 2.41, 95% CI = 1.12, 5.19 vs TYM > 42) or higher risk of malnutrition (MNA-SF ⩽ 11: aOR = 6.11, 95% CI = 3.15, 11.83 vs MNA-SF > 11). Conclusion: These findings suggest that the CDSMP intervention contributes to decreasing the self-perceived severity of frailty (SELFY-MPI score) in more vulnerable participants with several chronic diseases and lower cognitive performance and nutritional status.